2020
DOI: 10.1007/s00705-020-04777-2
|View full text |Cite
|
Sign up to set email alerts
|

Review of preventative HIV vaccine clinical trials in South Africa

Abstract: New HIV infections continue relentlessly in southern Africa, demonstrating the need for a vaccine to prevent HIV subtype C. In South Africa, the country with the highest number of new infections annually, HIV vaccine research has been ongoing since 2003 with collaborative public-private-philanthropic partnerships. So far, 21 clinical trials have been conducted in South Africa, investigating seven viral vectors, three DNA plasmids, four envelope proteins, five adjuvants and three monoclonal antibodies. Active v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
(121 reference statements)
0
20
0
Order By: Relevance
“…if companies do not innovate/manufacture and/or submit applications for marketing authorisations, medicines will not get approved irrespective of available regulatory resources. Most research and development activities take place outside of South Africa, although South Africa is very actively involved in clinical research [19,20]. The study only evaluated approvals and therefore does not take into consideration applications for registration of medicines which may have been removed by the applicant company or may have been rejected by the MCC.…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…if companies do not innovate/manufacture and/or submit applications for marketing authorisations, medicines will not get approved irrespective of available regulatory resources. Most research and development activities take place outside of South Africa, although South Africa is very actively involved in clinical research [19,20]. The study only evaluated approvals and therefore does not take into consideration applications for registration of medicines which may have been removed by the applicant company or may have been rejected by the MCC.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…South Africa is almost never in the first wave of countries in which companies seek registration for new medicines. However, South Africa is an active participant in international clinical trials on new treatments that are being developed for some of the top diseases that represent a high burden of disease in the country such as HIV/ AIDS and cancer [19,20]. Even so many of the treatments tested on patients during clinical trials conducted in South Africa do not eventually get registered in the country [21].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions based on demandside described findings including communication, education and information and peerbased interventions on outcome of HIV are unsatisfactory as they rarely reduce prevalence or incidence of HIV. Few studies and trials showed in reviews assessed interventions for increasing circumcision and pre exposure prophylaxis demand, though data from these components are still in emerging stage [110][111][112][113][114][115][116]. Additional research is needed for understating the reason of decreased uptake for these approaches and assessments needed for improved interventions to increase the adherence and uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Tested in phase I/IIa trials, this vaccine candidate has been shown to be safe and immunogenic 7 . Currently, this vaccine approach is undergoing two phase 2b-3 clinical evaluations in South Africa (HVTN 705) and the United States (MOSAICO) 8 . Another live vector that persists in the host, rhesus cytomegalovirus (RhCMV), has been evaluated in non-human primates challenged with SIVmac251 9 .…”
Section: Introductionmentioning
confidence: 99%